Городское пространство как поле мемориальных боев - Troitskiy, Sergey (Studia Rossica Posnaniensia, 2025)
In the proposed article, the author focuses on one of the complexes that make up the content of confrontations, namely the memorial complex, realised through the politics of memory on the part of the state, sometimes on the part of individual institutions of civil society. Historical memory is one of the instruments of influence, sometimes even more effective than solutions aimed at modernity. Memory politics is linked to constructing the past, which is actually alienated from the bearers of this past in order to influence (alienate) the present. The present is re-constructed through the politics of memory. Not surprisingly, it is on the memorial front that the fiercest battles for the present are fought. The confrontation between different collective actors, bearers of different memorial constructs, often turns into a "hot" phase, into a direct clash. Therefore, the phrase "memorial battles" in the title is not so much a literary metaphor as a description. The urban environment, due to its multiculturalism, is a space of confrontation between memorials, which is reflected in the urban landscape. This article considers two main tendencies, seemingly opposite, but in fact being different ways of realising one process - the construction of the history of the past. The text shows that these two tendencies are the construction of memory and cultural displacement.